2018
DOI: 10.1176/appi.ajp.2018.17121402
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Abnormalities in Never-Treated Patients With Long-Term Schizophrenia

Abstract: These psychoradiological findings provide insight into the regional distribution of white matter deficits in the years after illness onset in long-term schizophrenia. Findings of greater impairments in never-treated patients, and a greater age-related reduction in the genu of the corpus callosum in these patients, suggest that long-term antipsychotic treatment does not adversely affect white matter tracts over the longer-term course of illness and may confer benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 58 publications
(76 reference statements)
7
33
5
Order By: Relevance
“…It should be noted that unlike our previous findings that long-term untreated patients showed more severe deficits in the white matter 17 and functional networks 48 than treated patients, our findings revealed more regions with reduced GM in treated patients than untreated patients. One of the possible explanations is that the mechanism of antipsychotics may be associated with GM reductions and functional performance improvements.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It should be noted that unlike our previous findings that long-term untreated patients showed more severe deficits in the white matter 17 and functional networks 48 than treated patients, our findings revealed more regions with reduced GM in treated patients than untreated patients. One of the possible explanations is that the mechanism of antipsychotics may be associated with GM reductions and functional performance improvements.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown GM abnormalities in chronic schizophrenia [10][11][12][13][14][15] , but these studies have mostly been during the middle course of the illness. However, only two studies 16,17 reported GM alterations during a relatively later course of the illness. A cross-sectional brain structural study 16 found that, relative to healthy controls, schizophrenia patients with an untreated illness course of more than 20 years demonstrated less cortical thickness in the bilateral ventromedial prefrontal cortices, left superior temporal gyrus, and right pars triangularis and greater cortical thickness in the left superior parietal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of individuals with schizophrenia and healthy controls introduces an additional confounder of antipsychotic drug exposure, from which healthy controls are naïve. Antipsychotic drug exposure is correlated with a reduction in age-related FA decline in the corpus callosum in those with schizophrenia (Xiao et al, 2018), potentially via facilitation of oligodendrocyte regeneration and myelin repair following injury (Zhang et al, 2012). Although in the current study we found no correlation between chlorpromazine equivalents and corpus callosum FA, a comparison with healthy controls would likely suffer from some degree of interference from antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 77%
“…Collectively, both functional and structural connectivities between the left PCC and ACC may be related to the severity of symptoms as represented by delusions. Additionally, Yuan et al revealed that patients with schizophrenia who had never been treated for a long term showed more sever white matter abnormalities in the left cingulum-hippocampus pathway compared with patients with schizophrenia who had been treated [ 49 ]. This finding supports our hypothesis that the persistent symptoms observed in patients with TRS may be associated with functional abnormalities in the left cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%